2023
DOI: 10.3390/foods12091850
|View full text |Cite
|
Sign up to set email alerts
|

Carnauba Wax and Beeswax as Structuring Agents for Water-in-Oleogel Emulsions without Added Emulsifiers

Abstract: This research aims to explore the potential of waxes as ingredients in the formulation of food-grade water-in-oleogel emulsions without added emulsifiers. The effects of the wax type, wax concentration and water concentration were tested on systems containing exclusively water, sunflower oil, and wax. Beeswax and carnauba wax were used in the formulation of water-in-oleogel emulsions with 20%, 30% and 40% w/w of water. For the continuous phase, three different levels of wax were used, namely 50%, 100%, and 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…Given the composition of the CW (see Section Materials), these compounds tentatively involved the triterpenic alcohols, esters of triterpenic alcohols, aliphatic alcohols, and fatty acids. All these results contrast with the microstructure of the W/O emulsions formulated with 5% carnauba wax (40% water) or with 5% beeswax (20% water) developed through a pre-emulsification step (90 C) followed by dynamic crystallization step (5 C) (Penagos et al, 2023). These authors showed through PLM and confocal laser scanning microscopy, that the water droplets of the carnauba wax and beeswax W/O emulsions were stabilized by wax crystals surrounding the droplets (i.e., Pickering effect) and by a crystal network developed in the oil phase by the corresponding wax (Penagos et al, 2023).…”
Section: Stabilizing Mechanism Of the W/o Emulsions Developed By The Cwmentioning
confidence: 68%
See 4 more Smart Citations
“…Given the composition of the CW (see Section Materials), these compounds tentatively involved the triterpenic alcohols, esters of triterpenic alcohols, aliphatic alcohols, and fatty acids. All these results contrast with the microstructure of the W/O emulsions formulated with 5% carnauba wax (40% water) or with 5% beeswax (20% water) developed through a pre-emulsification step (90 C) followed by dynamic crystallization step (5 C) (Penagos et al, 2023). These authors showed through PLM and confocal laser scanning microscopy, that the water droplets of the carnauba wax and beeswax W/O emulsions were stabilized by wax crystals surrounding the droplets (i.e., Pickering effect) and by a crystal network developed in the oil phase by the corresponding wax (Penagos et al, 2023).…”
Section: Stabilizing Mechanism Of the W/o Emulsions Developed By The Cwmentioning
confidence: 68%
“…All these results contrast with the microstructure of the W/O emulsions formulated with 5% carnauba wax (40% water) or with 5% beeswax (20% water) developed through a pre-emulsification step (90 C) followed by dynamic crystallization step (5 C) (Penagos et al, 2023). These authors showed through PLM and confocal laser scanning microscopy, that the water droplets of the carnauba wax and beeswax W/O emulsions were stabilized by wax crystals surrounding the droplets (i.e., Pickering effect) and by a crystal network developed in the oil phase by the corresponding wax (Penagos et al, 2023). On the other hand, as previously indicated pentacyclic triterpenes like the ursolic acid, can develop W/O emulsions tentatively stabilized also through the Pickering effect (Liu et al, 2022).…”
Section: Stabilizing Mechanism Of the W/o Emulsions Developed By The Cwmentioning
confidence: 68%
See 3 more Smart Citations